Investigating the media power of a population health monitoring survey: case study of the NSW Schools Physical Activity and Nutrition Survey (SPANS) - Paola T. Espinel; Rachel Laws; Catriona Bonfiglioli; Louise L. Hardy; Lesley King (Elsevier, 2013)
Abstract Objective : To examine the extent and nature of news coverage of a government‐funded population monitoring survey of children and the potential implications of this coverage for public health advocacy. Methods : Case study of the NSW Schools Physical Activity and Nutrition Survey (SPANS), a population monitoring survey of school‐aged children's weight and weight‐related behaviours, conducted in 1997, 2004 and 2010. Printed news items from all Australian newspapers between January 1997 and December 2011 mentioning the survey findings were identified from the Factiva database and a descriptive analysis of the content conducted. Results : Overall, 144 news items were identified. The news angles focused mainly on physical activity/sedentary behaviour; overweight/obesity and nutrition; however these angles changed between 1997 and 2011, with angles focused on physical activity/sedentary behaviour increasing, compared with overweight/obesity and nutrition angles (p=0.001). Responsibility for obesity and weight‐related behaviours was most frequently assigned to parents and food marketing, and the most common solutions were policy strategies and parental/child education and support. Conclusions : Population health surveys are newsworthy and when coupled with strategic dissemination, media can contribute to communicating health issues and interpreting findings in ways that are relevant for consumers, policy makers and stakeholders. Implications : This case study emphasises the news value of government‐funded population surveys, while providing a cautionary note about media focus on individual studies rather than a larger body of research evidence.